Enterprise Surveys : Slovenia Country Profile 2013 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The country profile for Slovenia is based on data from the enterprise surveys conducted by the World Bank. The country profiles provide an overview of key business environment indicators in each country, comparing them to their respective geographic region and group of countries with similar incomes. The benchmarks include the averages for the group of countries in Eastern Europe and Central Asia and the Slovenia income group. The topics covered include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business. Breakdowns by firm size are presented in the appendix along with all indicators used to make the graphs.